Cambodia : Staff Report for the 2000 Article IV Consultation and First Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2000)
The government embarked on a reform program in early 1999 to revive the momentum and policy measures that had been interrupted in 1997 and 1998 owing to the regional financial crisis and internal political turmoil. Monetary and exchange rate policies in 1999 were also supportive of improved economic conditions. The 17 percent increase in broad money was fully reflected in an increase in net foreign assets. Executive Directors welcomed Cambodia's improved macroeconomic performance and progress with structural reforms, which has helped increase confidence considerably.